Project Censored: The News That Didn't Make The News: founded by Carl Jensen at Sonoma State University in 1976. Issue 4 (2nd October 2022) - McDonald, Jeff
Abstract : Jeff McDonald is an investigative reporter for the San Diego Union-Tribune. He was named Journalist of the Year in 2015 by the local chapter of the Society of Professional Journalists for exposing an illegal deal to shut down a nuclear plant that shifted billions of dollars in costs from utility shareholders to ratepayers. McDonald also received a career achievement award from the San Diego Press Club last year in recognition of his two decades of coverage on waste and abuse in state and federal government, the high number of deaths in county jails, and wildly inflated city real estate purchases .